Strategi Integrated Marketing Communication dalam Optimalisasi Media Sosial pada Industri Jasa Transportasi CV Dita Trans - Ananda Dias Priyadi (CV. ITTC INDONESIA, 2026)
The rapid development of digital technology has forced conventional businesses to adapt their communication strategies to remain competitive. This study explores the implementation of Integrated Marketing Communication (IMC) in optimizing social media platforms for CV Dita Trans, a car rental service provider in Surabaya. Utilizing a qualitative descriptive approach and case study methodology, the research examines the transformation of the company’s digital presence through a four-week intervention. Initial audits revealed significant challenges, including visual inconsistency, lack of structured content, and slow response times in customer interaction. By applying IMC principles specifically integrating interactive marketing, public relations, and advertising the study demonstrates how structured content calendars, professional visual branding using digital tools, and improved response protocols can enhance brand image and customer trust. The findings indicate that the synchronization of visual identity across Instagram and TikTok, combined with data-driven posting schedules, significantly improves engagement metrics. This research highlights the critical role of consistent digital communication in the transportation sector, where reliability and responsiveness serve as the primary drivers of consumer decision-making in an increasingly competitive digital marketplace.